2011
DOI: 10.2147/ijn.s26306
|View full text |Cite
|
Sign up to set email alerts
|

Long-circulating delivery of bioactive polysaccharide from radix ophiopogonis by PEGylation

Abstract: Background: Radix ophiopogonis polysaccharide (ROP) has been found to be effective against myocardial ischemia. One of main problems with its use is its short in-vivo half-life, which makes the development of an effective delivery system necessary. To achieve better therapeutic effects and patient compliance by prolonging its retention in plasma and increasing its distribution in targets, ROP was PEGylated (PEG, polyethylene glycol) in this study. Methods: Through a moderate coupling reaction between hydroxyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In comparison, liposomes (~100 nm) displayed slower and more restricted extravasation from the vasculature and are therefore an attractive vehicle for the delivery of proangiogenic drugs. 29 In the present research, the PEG-ROP conjugates, with a hydrodynamic size approximately or beyond 10 nm, 21 were studied in parallel on the rat models of both MI and IR to clarify their ability to accumulate in the ischemic myocardia via the EPR effect. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, liposomes (~100 nm) displayed slower and more restricted extravasation from the vasculature and are therefore an attractive vehicle for the delivery of proangiogenic drugs. 29 In the present research, the PEG-ROP conjugates, with a hydrodynamic size approximately or beyond 10 nm, 21 were studied in parallel on the rat models of both MI and IR to clarify their ability to accumulate in the ischemic myocardia via the EPR effect. …”
Section: Discussionmentioning
confidence: 99%
“…Permanent ligation and transient ligation of the left coronary artery were adopted to induce the aforementioned two clinically relevant pathological statuses of myocardial ischemia in rats, respectively. To determine the effect of the molecular size of conjugates, two representative conjugates (ie, 20-and 40-kDa PEG mono-modified ROPs), whose values are around the midpoint and the upper inflection point of the sigmoidal-shaped profile of plasma half-lives versus apparent molecular weights, respectively, 21 were studied in parallel at three time points postdose after a sensitive and specific method for determining them quantitatively in biosamples was established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] Here, we designed a novel investigation method to intensively research the widely used PEGylation strategy. Kataoka and colleagues [22][23][24] reported that polyion complex (PIC) micelles prepared from polymers with opposite charges were efficient nanocarriers for drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Injectable long-acting systems for radix Ophiopogonis polysaccharide for polymeric conjugation because of its unique advantages: 22 little antigenicity, immunogenicity, and toxicity; high solubility in many solvents; highly hydrated and flexible backbone; and approval by the US Food and Drug Administration for human use in injectables. PEG and its conjugates are cleared from the body mainly by the kidney, and the excretion rate has a sigmoidal relationship with the molecular weight of the polymer, showing a greatly reduced rate over approximately 40 kDa.…”
mentioning
confidence: 99%